The Role of Leadership for Improving the Quality and Performance of Health Services in Primary Health Care : A Literature Review - Oktanti, Qoni (Department of Public Health, Faculty of Health Sciences, Jenderal Soedirman University, 2024)
Background: Community Health Centers or we usually called Puskesmas in Bahasa, as first-level health facilities, have a great responsibility in providing quality health services to the community. In carrying out this function, the role of leadership is a key factor that influences the effectiveness and efficiency of services. Strong and effective leadership in Community Health Centers could encourage the achievement of organizational goals, such as increasing service accessibility, reducing morbidity and mortality rates, and also increasing patient satisfaction. This study aims to examine how the role and style of leadership in Community Health Centers can affect the quality of health services provided. Methods: A systemic literature review was conducted of the published articles in 2015-2025. Published articles included journals, papers and issue briefs. The determination of the article is based on the purpose of writing, namely to determine the influence and various leadership styles on improving the quality of services at the Community Health Center. Results: The influence of a good leadership role not only affects the performance of health center officers, but also has a positive effect on patient satisfaction with a health service, the improvement of the quality of services, the competence and also the infrastructure. Various leadership styles can be optimally adjusted to different leaders and health center conditions. Conclusions: Leadership has a very important influence on improving the quality of services in the Health Center, where it can be assessed from the improvement of the performance of health workers in the Health Center, patient satisfaction and also the quality of health center services. There are also various leadership styles, but a good leadership style is a flexible one that it could be adjusted to the situation and conditions in the health center.